Pengaruh Penggunaan Media Pembelajaran Animasi Powtoon terhadap Kecerdasan Visual Spasial Siswa Pada Mata Pelajaran Matematika Kelas VI MI Miftahul Khoer - Indra Saeful Hidayat; Agus Abdullah Ashari (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
This research was conducted at MI Miftahul Khoer, Kumpay village, Jalancagak. This research is a quantitative research with a Quasy Experiment type or research. The population in this study were all students of MI Miftahul Khoer, totalling 200. The sample of this study consisted of 1 class totalling 30 students and divided into 2 groups consisiting of an experimental group with 15 students and a control group with 15 students person. The test instrument used to determine the visual-spatial intelligence of science subjects was a multiple choice test in the form of a post-test which consisted of 10 questions. The data analysis technique used in this study used the t test. Based on the research that has been carried out, it can be concluded that there is an influence of powtoon animation learning media on the visual spatial intelligence of students in mathematics at MI Miftahul Khoer.